An attempt at the characterisation of the development of modern sports gymnastics - Zasada, M. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2006)
The scientific verification, the synthesis and the analysis of practical as well as theoretical information provide us with a basis for assessing and formulating a number of factors which influence the development of sports gymnastics. The aim of the article is an attempt at characterising the development of modern sports gymnastics. The following conclusions result from theoretical analysis of the literature which has been available for the last few years, the analysis of the training process of Ukrainian and Russian gymnasts, as well as my own experience gained both as a trainer and a competitor and a long-term researcher interested in our leading Polish gymnasts. The main developmental tendencies concern: an individual`s attitude towards the training process, the intensification of the training, a faster mastering of the sports programs owing to the constant development of the methodology, the importance of physical training of the athletes, the unification of the training technology of the gymnasts who represent the advanced level, the improvement of the means which make the training work safer, and a scientific study of the main components of the training technology.